Comparative study of Low-level laser therapy and microcurrent on the healing of skin burns in rats - Rodrigo Pegado de Abreu Freitas; Aline Barbosa Macedo; Anderson Rodrigues de Oliveira; Ana Maria de Oliveira Ramos; Wouber Hérickson de Brito Vieira (Acta Scientiarum. Health Sciences, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.14668This study investigated and compared the effects of low-level laser therapy (LLLT) and microcurrent in the burn healing process in Wistar rats. We conducted a randomized controlled study with 30 rats divided into 3 groups (n = 10); control group (CG), laser group (LG) and microcurrent group (MG). After thermal damage, 10 applications of 660 nm diode laser were performed in GL and 10 applications of 60 Hz microcurrent (160 μA) in MG. The semi-quantitative histological analysis was done using scores (0–3), in sections stained by hematoxylin and eosin and Masson’s trichrome. The results indicated a significant improvement in the fibroblasts proliferation, collagen fibers deposition, neoangiogenesis, and cutaneous appendages regeneration in MG and LG. When microcurrent and LLLT were compared, no difference was detected, except the regeneration and formation of new cutaneous appendages, observed in MG. Despite the similar effects, GM showed faster tissue repair with the formation of skin appendages.